2019
DOI: 10.1016/j.rbms.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A wonderful experience or a frightening commitment? An exploration of men's reasons to (not) have children

Abstract: Research on reproductive decision-making mainly focuses on women's experiences and desire for children. Men included in this type of research usually represent one-half of a heterosexual couple and/or men who are involuntarily childless. Perspectives from a broader group of men are lacking. This study is based on the results of a baseline questionnaire answered by 191 men aged 20-50 years who attended two sexual health clinics in two major Swedish cities. The questionnaire included questions about sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…7 The majority of people aspire to have children and it is known that men desire parenthood as much as women do. [8][9][10] Nonetheless, the impact of IA on one of the most important markers of fertility, the male fertility rate (total number of children per man), [11][12][13] has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The majority of people aspire to have children and it is known that men desire parenthood as much as women do. [8][9][10] Nonetheless, the impact of IA on one of the most important markers of fertility, the male fertility rate (total number of children per man), [11][12][13] has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Childbearing decisions and reproductive potential are strongly influenced by multiple psychosocial, demographic and biological factors. 9 14 Furthermore, it has been demonstrated that men diagnosed with chronic diseases are exposed to additional factors that have an effect on their childbearing decisions and their reproductive potential. 15 16 …”
Section: Introductionmentioning
confidence: 99%
“…Men expressed a wish to shape a child and regarded parenthood as psychologically and personally fulfilling. The views of parenthood for men were often related to their own upbringing and family ties (Bodin, Plantin, & Elmerstig, 2019). Additionally, the social roles of men have been changing over time.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, most couples are too busy with work so they don't have time to think about the children. [17] 4. Philosophical Among the adherents of childfree, they think what is the true meaning of children and offspring.…”
Section: Economy and Culturementioning
confidence: 99%